Archaeologies of post-socialist temporalities: Documentary experiments and the rhetoric of ruin gazing. Issue 1 (2nd January 2019) - Huang, Erin Y.
Abstract: Focusing on the independent documentary movement that is also a movement of digital filmmaking in China, this essay examines documentary's mediation of post-socialist conceptions of time through digital filmmaking aesthetics, including ruin gazing, forwarding and reversing, and accelerating and decelerating film speed. In a comparative study of experimental documentaries on post-socialist temporalities in Eastern Europe and China—including the work of Chantal Akerman, Cong Feng, and Huang Weikai—the essay unravels documentary's representation of time that illustrates the "post" as a locus of desires and anxieties, backward and forward glances that create heterogeneous relationships—with their own economy of stasis, velocity, and speed—in relation to the homogeneous and teleological time of Capital.